The Galatheidae (Anomura: Galatheoidea) of South Africa, with a description of a new species - Botha, Thomas P A; Griffiths, Charles L; Atkinson, Lara J; Macpherson, Enrique (Zootaxa, 2025)
Squat lobsters of the family Galatheidae are severely understudied in South Africa and have never been the subject of a regional monographic study. The last additions and updates to the fauna were made almost 20 years ago and a revision of this family is thus long overdue. This study adds to, revises and updates the regional fauna based on examination of historic material housed in the Natural History Collections of the Iziko South African Museum, as well as ad-hoc samples collected around the South African coast. A new species of Galathea Fabricius, 1793 is described and illustrated, while three other species are added to the regional fauna and several dubious records resolved. The taxonomic status of Galathea labidolepta Stimpson, 1858 is confirmed and the species redescribed, with a neotype being assigned to replace the holotype lost in the 1871 Chicago fire, and a species of the genus Lauriea Baba, 1971 is reported for the first time from the country. A dichotomous key for identification of all species found in South Africa is also included. Although this study adds substantial knowledge on the group, it also highlights the need for more rigorous sampling in South Africa.